What do we know about reading and spelling in shallow orthographies? - Schmalz, Xenia (Revista de Investigación en Logopedia, 2025)
Reading and spelling research has traditionally been centred on English, despite its significant differences from other European orthographies. This anglocentric focus raises questions about the generalisability of reading theories to alphabetic orthographies more broadly. Understanding cross-linguistic differences in reading acquisition is crucial, given the practical implications for literacy instruction and dyslexia intervention. Shallow orthographies enable faster mastery of grapheme-phoneme correspondences, while deep orthographies may necessitate stronger reliance on alternative strategies such as lexical guessing and reliance on larger sublexical units. The cognitive mechanisms underlying fluency development, particularly the role of high-quality lexical representations, provide open research questions for further research. Spelling accuracy is also affected by orthographic depth, with greater challenges in deep orthographies due to ambiguous phoneme-grapheme mappings. While phonics instruction is well-established, research on enhancing lexical processing to support reading fluency and spelling acquisition is limited. This paper synthesises current cross-linguistic findings, highlights gaps, and discusses practical implications for literacy instruction across alphabetic orthographies.
Keywords: Orthographic learning; Orthographic Depth Hypothesis; Reading aloud; Spelling